MANAJEMEN PROGRAM HIMPAUDI DALAM PENINGKATAN KUALITAS PENDIDIK PAUD DI KOTA BANDAR LAMPUNG - Intan Permata Hati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study is motivated by the importance of effective management of HIMPAUDI programs in improving the quality of early childhood education (PAUD) educators, which directly impacts the quality of early childhood education services in Bandar Lampung City. The purpose of this research is to analyze how the management of HIMPAUDI programs is carried out systematically and structurally to optimally enhance the competence and professionalism of PAUD educators. This study uses a descriptive qualitative research approach. The research subjects are HIMPAUDI administrators and PAUD educators in Bandar Lampung City, while the research object is the management of HIMPAUDI programs. Data collection techniques include interviews, observations, and documentation. The collected data were then analyzed using qualitative descriptive methods through the stages of data reduction, data presentation, and verification to draw valid conclusions. The results of the study show that: (1) In planning, HIMPAUDI actively identifies training needs based on factual conditions in the field, develops training work programs based on PAUD Teacher Competency Standards, and considers the availability of relevant time and resources. (2) In organizing, HIMPAUDI establishes a clear implementation team structure, coordinates effectively with related stakeholders, and provides adequate training facilities and media. (3) In implementation, HIMPAUDI successfully carries out training programs according to schedule and curriculum, involves professional resource persons, and provides continuous motivation and mentoring to training participants. (4) In supervision, HIMPAUDI conducts periodic evaluations of training implementation, collects feedback from participants and resource persons, and follows up with mentoring programs and advanced training to ensure the sustainability of educators’ competency improvement. The study also found that HIMPAUDI integrates a needs- based and results-oriented approach, making its programs more adaptive and contextual.